The Influence of Perceived Quality, Brand Equity, Brand Image and Brand Trust on Customer Brand Loyalty (Study at Sulutgo Bank in Manado City) - Adolf, Nanlohy Jay; Kindangen, Paulus; Saerang, Ivonne Stanley (Research Parks Publishers, 2023)
The phenomena or problems that exist so that this research is raised are due to the rise of skimming banking crimes or acts of theft of information or breaking into accounts by illegally copying data contained on the magnetic stripe of credit or debit cards. This was experienced by a customer from SulutGo bank some time ago.This can have an impact on the condition of SulutGo Bank because when customers do not feel comfortable and safe, customers are no longer loyal. This study aims to determine the effect of perceived quality, brand equity, brand image and brand trust on brand loyalty. The analytical method used is multiple linear regression. The results of the hypothesis test found that simultaneously perceived quality, brand equity, brand image and brand trust on brand loyalty, but partially perceived quality has no effect on brand loyalty. The result of the correlation coefficient or R is 0.560, this indicates that the influence between perceived quality (X1), brand equity (X2), brand image (X3) and brand trust (X4) to brand loyalty (Y) for Bank Sulutgo customers, the main branch in Manado City, has a moderate relationship of 56%. It can also be seen that the results of the coefficient of determination or R square (r2) is 0.612 which indicates that 61.2% of brand loyalty (Y) is influenced by perceived quality (X1), brand equity (X2), brand image (X3) and brand trust (X4). ) while the remaining 38.8% is influenced by other variables not examined in this study. For the Sulutgo bank, the main branch in Manado City, to pay more attention to factors such as perceived quality, brand equity, brand image and brand trust.